Karl Marx entre a crítica da religião e do colonialismo: dialética e fetichismo no livro I de O Capital - Andrade, Douglas Sobrinho de (2023)
What method did Karl Marx mobilize in his critique of political economy? Considering Marx's own notes, this method would appear, above all, after 1857. In this sense, this work sought to understand the dialectical method as a critical exposition of the system of bourgeois economy. Understanding the limits of dialectics as a critical exposition, we advanced on the relationship of materialist dialectics with the Marxian theory of fetishism. Consequently, we understand the theory of fetishism as the methodological tool that points out, within the architectural structure of the first book of Capital, the necessary historical presupposition of critical exposition. With this scope, our work analyzed the preparatory texts of Capital I and its first chapter. Thus, we realized that the simple circulation, that is, the first chapters of Capital I, presupposes the original accumulation that only appears in the last act of this exposition. As an unfolding of the relationship between dialectics and fetishism, we also investigate the Marxian critique of religion and critique of colonialism. Just as Marx was interpellated by the political struggles of his time, we attempt to interpellate the Marxian text on the ambiguous role of religion as expression and protest, based on the struggles of liberation Christianity in Latin America. Furthermore, we investigate Marx's evolution in the evaluation of colonialism, perceiving the colonial system precisely as the historical presupposition of capitalism.